Evacuation of people in case of fire of the public bus transport class II-III. Analysis of evacuation using the experimental data of movement of people and fire simulation results - Ivanitskiy Александр; Botyan Сергей (Vestnik of the Institute for Command Engineers of the MES of the Republic of Belarus, 2015)
Research work shows all statistical data related with amount of fires which happened in buses and analysis of its reasons and results. Influence of bus cabin’s constructional features on evacuation process was considered. The actual evacuation time from bus cabin was experimentally determined, using the methodology of experimental studies (were previously developed), based on special algorithm of stage-by-stage evacuation. These research results were compared with time of achievement maximum permissible values of dangerous factors of the fire, based on results of fire dynamics modeling in the bus. Thus, the major hazardous fire factors were defined.